(untitled) (Experimental biology, 2009)
By using a RT-PCR strategy two cellulase cel7A and cel6B cDNA genes from Shiitake mushroom Lentinulla edodes were amplificated. It has been shown that products of their translation belonged to glycosyl hydrolase family 7 and 6 and had sequence similarities to cbhII genes from other fungi.